The Role of Content Marketing on TikTok in Increasing Sales - Gisha, Nadia; Malinda, Maya (Proceedings International Conference on Education Innovation and Social Science, 2023)
This research explores the impact of content marketing strategies on TikTok in increasing sales of the local brand "shayn". Two content marketing techniques, creative content without using advertising and using advertising, and their effectiveness are analyzed. These findings were obtained through a quantitative research approach and descriptive statistical analysis, the results show that leveraging creative content without advertising on TikTok can effectively increase brand awareness and generate sales, even with limited resources. This study emphasizes the importance of creating relevant and interesting content tailored to specific market segments. Active brand engagement on TikTok has also proven important in increasing brand visibility and attracting potential customers. This insight has valuable implications for brands looking to leverage TikTok as a platform for content marketing and sales growth.